Oncocytic Adrenocortical Neoplasm Diagnosed after Robot-Assisted Adrenalectomy - Andrew C. Harbin; Andrew Chen; Siddharth Bhattacharyya; Jasvir S. Khurana; Joshua R. Kaplan; Daniel D. Eun (Case Reports in Urology)
Oncocytic tumors, composed of eosinophilic, mitochondria-rich cells, can occur in several locations throughout the body. These tumors can occur in the adrenal cortex and are rarely malignant. We report a case of a patient presenting with an incidental adrenal mass which was later diagnosed as a oncocytic adrenocortical neoplasm (OAN). The patient is a 53-year-old man found to have a 7.2 cm right adrenal mass, incidentally found by computed tomography (CT). After metabolic workup was negative, a right robotic adrenalectomy (RA) was performed. Pathologic analysis revealed clusters of large cells with abundant eosinophilic and granular cytoplasm, consistent with OAN. This pathology is rare, with only about 150 cases described in the literature. It occurs in females 2.5 times more frequently and more commonly on the left side. Diagnosis is usually made by imaging criteria, typically with CT or magnetic resonance imaging (MRI). Treatment is generally surgical, since OAN can be malignant in some cases. Differentiation between benign and malignant OAN is done based on the Lin-Weiss-Bisceglia criteria and can be difficult. If malignancy is diagnosed, recurrence is common and close surveillance should be performed.